The Marginal Cost of Public Funds in Africa - Warlters, Michael; Auriol, Emmanuelle (World Bank, Washington, DC, 2012)
The authors use a computable general equilibrium model to estimate the marginal cost of public funds (MCF) for taxes on domestic goods, exports, imports, capital, and labor in 38 African countries. The resulting MCF estimates provide directions for tax reform in Africa. The authors investigate the MCFs of hypothetical taxes in the informal sector and the impact of administrative costs. Finally, they investigate the relationship between MCF dispersion and measures of tax system inefficiency.